Management of early loss of first permanent molar: A new technique - B S Rajashekhara; J M Keyur; D Bhavna; K S Poonacha (Wolters Kluwer Medknow Publications, 2012)
The loss of a permanent first molar in adolescent patient creates a need for early space maintenance and restoration of function. To ascertain function and esthetics, immediate treatments include interim restorative approaches. This paper describes a conservative, functional and cost-effective bridge as an interim restoration after the loss of permanent first molar in an early adolescent dentition.